PENGARUH INFLUENCER MARKETING TERHADAP BRAND AWARENESS DAN PURCHASE INTENTION PRODUK SKINCARE TRUE TO SKIN PADA MEDIA SOSIAL TIKTOK - Yeni Dwi Atika; Dita Puruwita; Nofriska Krissanya (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2025)
This study aims to examine the effect of Influencer Marketing on Brand Awareness and Purchase Intention of true to skin skin skincare products on Tiktok social media. The method used is quantitative research with a survey approach. The research population is skincare users aged 18-34 years in the Bekasi City area who have an interest in buying true to skin skincare products on TikTok social media. The sampling technique used a non-probability purposive sampling method with a total of 120 respondents. Data was obtained through a closed questionnaire using a Likert scale. Data processing was carried out using the Structural Equation Modeling (SEM) method with the Partial Least Squares (PLS) approach using SmartPLS version 4 software, with indicators VIF, R-square, effect size (F2), Q-square (Q2), Goodness of Fit (GoF). The results showed that Influencer Marketing has a positive and significant effect on Purchase Intention, and Brand Awareness. Brand Awareness has a positive and significant effect on Purchase Intention. In addition, Brand Awareness plays a significant role in mediating the influence of influencer marketing on Purchase Intention.